Factors influencing user interest in using Sharia-compliant Fintech services: A case study of SyarQ in Yogyakarta, Indonesia - Yuniati, Tri; Andriansyah, Yuli; Martins, José Duarte Moleiro (Journal of Islamic Economics Lariba, 2024)
IntroductionThe rapid growth of financial technology has led to the emergence of sharia-compliant services like SyarQ, an Islamic-based online installment platform. Understanding the factors that influence consumer interest in such services is essential for their adoption and success.ObjectivesThis study aims to analyze the factors affecting users' interest in using SyarQ's services by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB).MethodA quantitative and exploratory research design was employed, utilizing online questionnaires distributed to 100 verified SyarQ users. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses and examine the relationships between variables.ResultsThe findings reveal that user attitude has a positive and significant effect on the interest in using SyarQ services. Perceived behavioral control positively influences perceived ease of use but does not significantly affect interest directly. Perceived ease of use positively affects both attitude and perceived usefulness. Subjective norms have a positive and significant impact on perceived usefulness but do not significantly influence interest. Perceived usefulness does not have a significant effect on attitude or interest.ImplicationsThe study suggests that enhancing user attitudes and simplifying the user experience can increase consumer interest in Sharia-compliant fintech services like SyarQ. Providers should focus on improving the ease of use and addressing factors that positively influence user attitudes to attract and retain customers.Originality/NoveltyThis research contributes to the existing literature by combining TAM and TPB to examine user interest in a Sharia-compliant fintech platform. It offers valuable insights into consumer behavior within Islamic financial services, a relatively underexplored area.